Effects of Personalized Nursing Combined With Mindfulness-Based Stress Reduction on Anxiety, Depression, and Quality of Life in Patients With Pneumonia-Induced Sepsis. - Zheng, Xinrong; Zhang, Qijun; Zhuang, Hesheng (Actas Espanolas de Psiquiatria, 2026)
Background: This study aimed to investigate the effects of personalized nursing combined with MindfulnessBased Stress Reduction (MBSR) on anxiety, depression, self-efficacy, quality of life and self-care ability in patients with pneumonia-induced sepsis. Methods: This retrospective study enrolled 127 patients with pneumonia-induced sepsis admitted between July 2023 to July 2024. Among them, 59 patients in the routine nursing group received routine nursing care, while 68 patients in the combined nursing group received personalized nursing combined with MBSR. Routine nursing included vital signs monitoring, oxygen therapy, medication management, basic daily care, nutritional support, health education and complication prevention. The combined nursing group additionally received personalized nursing (e.g., psychological assessment and support, targeted health education, and dynamic adjustment of care plans) and MBSR training (e.g., mindful breathing, body scanning, mindfulness meditation and relaxation training), delivered daily or several times per week until discharge. Outcome measures included the Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale (HAMD), General Self-Efficacy Scale (GSES), World Health Organization Quality of Life-100 (WHOQOL-100), and Exercise of SelfCare Agency (ESCA), assessed before and after nursing measures. Categorical variables were compared using the chi-square test, and continuous variables (mean ± standard deviation) were analysed using independent-samplest tests. Results: No statistically significant baseline differences in demographic or clinical characteristics were observed between the two groups (p > 0.05). After nursing measures, both groups showed improvements in HAMA, HAMD, GSES, WHOQOL-100, and ESCA scores compared with baseline. The combined nursing group demonstrated significantly greater reduction in HAMA and HAMD scores (p < 0.05) and significantly greater increases in GSES, WHOQOL-100, and ESCA scores (p < 0.05) than the routine nursing group. Conclusions: An integrated approach combining personalized nursing and MBSR was associated with lower levels of negative emotional states, higher self-efficacy in disease management, and better quality of life and self-care ability in patients with pneumonia-induced sepsis. These findings suggest that this nursing model may represent a feasible and potentially beneficial strategy for improving psychological and functional outcomes in clinical practice.